Financial Resilience and Cash Flow Volatility: Strategies to Improve the Financial Performance of Manufacturing Companies - Tabah Rizki; Amirul Bahar (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2026)
This study aims to analyze the effect of financial resilience (FR) and cash flow volatility (CFV) on financial performance, as measured by Return on Assets (ROA), in manufacturing companies in Indonesia during the period 2020–2024. The study uses a descriptive quantitative approach with secondary data from 200 observations of financial statements. The analysis was conducted using multiple regression to test the partial and simultaneous effects of FR and CFV on ROA. The results show that financial resilience has a positive and significant effect on financial performance, while cash flow volatility has a negative and significant effect. Simultaneously, FR and CFV were proven to have a significant effect on ROA, emphasizing the importance of integrated management of financial resilience and cash flow stability. These findings provide an understanding that companies that are able to maintain financial resilience while stabilizing cash flow not only increase profitability but are also able to minimize liquidity risk, reduce revenue uncertainty, and reduce potential conflicts of interest between managers and shareholders, resulting in more sustainable financial performance.